Exhaustions of the non-object = Beckett: A hermeneutic reading of Deleuze’s "L’épuisé" - Badal Casas, Laia (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
In this article we analyse the text of L’épuisé, by Gilles Deleuze, from hermeneutics. We start from his definition of the figure of the "exhausted" as something that destabilizes the hegemonic logic of the structures of language, and we generate a rhizomatic dialogue between this figure and Deleuze’s thinking by summoning several of the publications and reflections of his entire career. The reflection on language, on literature and art as spaces of détournement and on some bases of post-structuralism finally give way to the analysis of four filmed works by Samuel Beckett, which help to put into practice the theories formulated by Deleuze in the whereas they rub against them from their singularity, and from their own formulas of language exhaustion.